Investigation of Microstructure and Corrosion Resistance of Dissimilar Welded Joint between 304 Stainless Steel and Pure Copper - Sorush Niknamian (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Nowadays, welding of dissimilar metals has become significant. In this process, a number of parameters including but not limited to type of electrode, amount of current, preheating temperature, and welding rate, that are essential to be taken into account. For welding of dissimilar metals, various methods are exploited including shielded metal arc welding (SMAW) and gas tungsten arc welding (GTAW). The stimulus for studying welding of 304L stainless steel to pure copper originates from difficulties in joining copper parts of           water-circulating molds to their steel part. In this study, the welding is performed on plates of steel and copper using SMAW, GTAW and combined SMAW+GTAW welding methods with    EL-CuMn2, ENiCrMo-6 and ER70S-4 electrodes. In order to investigate the microstructure and corrosion resistance behavior of welds, the samples were characterized using microstructural study and polarization test. It was observed that among all four welding methods, only combined SMAW+GTAW welding process resulted in successful joint between 304L stainless steel and copper. Both obtained joints possess suitable microstructure and corrosion resistance.